2001
DOI: 10.1161/hc4301.098252
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin Contributes to the Vasodilator Effects of Chronic Angiotensin-Converting Enzyme Inhibition in Patients With Heart Failure

Abstract: Background-Bradykinin, an endogenous vasodilator peptide, is metabolized by ACE. The aims of the present study were to determine the doses of B9340, a bradykinin receptor antagonist, that inhibit vasodilatation to exogenous bradykinin and to assess the contribution of bradykinin to the maintenance of basal vascular tone in patients with heart failure receiving chronic ACE inhibitor therapy. Methods and Results-Forearm blood flow was measured using bilateral venous occlusion plethysmography. On three occasions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
2
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 42 publications
3
70
2
1
Order By: Relevance
“…In patients with CHF who received long-term ACEI therapy, a B 2 receptor antagonist had no discernible vasoconstrictive effects on forearm blood flow; 22 conversely, a combined B 1 and B 2 receptor antagonist produced vasoconstriction. 23 In the present study, we did not verify the role of B 1 receptors in the vasculature; however, in our tachycardia-induced CHF model, which is quite similar to the clinical findings of the dilated cardiomyopathy seen in humans, endogenous BK did not appear to participate in arterial blood pressure regulation, at least via a B 2 receptor.…”
Section: Discussioncontrasting
confidence: 71%
“…In patients with CHF who received long-term ACEI therapy, a B 2 receptor antagonist had no discernible vasoconstrictive effects on forearm blood flow; 22 conversely, a combined B 1 and B 2 receptor antagonist produced vasoconstriction. 23 In the present study, we did not verify the role of B 1 receptors in the vasculature; however, in our tachycardia-induced CHF model, which is quite similar to the clinical findings of the dilated cardiomyopathy seen in humans, endogenous BK did not appear to participate in arterial blood pressure regulation, at least via a B 2 receptor.…”
Section: Discussioncontrasting
confidence: 71%
“…Angiotensin-I converting enzyme (ACE) plays an important role in the regulation of blood pressure and hypertension because catalyzes the conversion of inactive angiotensin-I into angiotensin-II, a potent vasoconstrictor (Goodfriend, Elliott & Catt, 1996) and inactivates bradykinin, a potent vasodilator (Witherow, Helmy, Webb, Fox & Newby, 2001). Synthetic inhibitors of ACE are often used to treat hypertension (Pahor, Psaty, Alderman, Applegate, Williamson & Furberg, 2000) and other cardio-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In patients with HF chronically treated by ACE inhibitors, BK receptor blockade with a mixed B1 and B2 receptor antagonist produces a dosedependent vasoconstriction that disappears after withdrawal of ACE inhibitor therapy, suggesting a role of BK at the vascular level in the chronic treatment with these drugs. 5 In the coronary circulation, previous studies have shown that BK participates in the regulation of coronary vascular tone 6 and improvement of coronary endothelial dysfunction and coronary flow reserve by ACE inhibitors. 7,8 Recent studies have demonstrated that, in contrast with the impaired vasodilator response to acetylcholine usually observed in HF, 9 -11 the vasodilator effect of exogenous BK is preserved in pacing-induced HF in dogs 4 and that endogenous BK plays a significant role in the vasomotor control in HF.…”
mentioning
confidence: 99%